Psychometric properties of the self-efficacy scale for chronic disease management (SEMCD-S) in older Colombian adults (2023)
Background Self-efficacy alludes to personal competence in an individual’s effectiveness when facing stressful situations. This construct has been related to different domains of the health field, finding that high levels of self-efficacy benefit human functioning and enhance well-being. Methods The present study aimed to determine the psychometric properties of the self-efficacy scale for managing chronic diseases (SEMCD-S) by assessing factorial, convergent and divergent validity, reliability, and measurement invariance. Likewise, the comparison of self-efficacy according to socio-demographic characteristics was proposed by contrasting latent factors. An instrumental, transactional, descriptive, and non-experimental design study was carried out with the participation of 325 Colombian senior citizens. Results The findings suggest that the scale has appropriate psychometric properties. The one-factor structure exhibited a satisfactory fit, the mean-variance extracted reported acceptable figures and the correlation analysis with other constructs supported this instrument’s convergent and discriminant validity. Likewise, it was invariant to the different socio-demographic aspects examined, while the internal consistency figures were high. Differences in the means of the latent factors were only detected in the academic grade. In this case, older adults with a primary school level attained higher self-efficacy values than those who had completed high school or university studies. Conclusions It is concluded that the self-efficacy scale for chronic disease management is a valid and reliable instrument that can be used in the Colombian context to measure and compare this construct.